Biomarkers in adult asthma: a systematic review of 8-isoprostane in exhaled breath condensate. (10th February 2017) - Peel, Adam M; Crossman-Barnes, Christina-Jane; Tang, Jonathan; Fowler, Stephen J; Davies, Gwyneth A; Wilson, Andrew M; Loke, Yoon K
Abstract: Objectives. We aimed to assess the evidence for the use of 8-isoprostane in exhaled breath condensate (EBC) as a biomarker in adult asthma. Design. A systematic review and meta-analysis of EBC 8-isoprostane. Methods . We searched a number of online databases (including PubMed, Embase and Scopus) in January 2016. We included studies of adult non-smokers with EBC collection and asthma diagnosis conducted according to recognised guidelines. We aimed to pool data using random effects meta-analysis and assess heterogeneity using I 2 . Results. We included twenty studies, the findings from which were inconsistent. Seven studies ( n  = 329) reported 8-isoprostane levels in asthma to be significantly higher than that of control groups, whilst six studies ( n  = 403) did not. Only four studies were appropriate for inclusion in a random effects meta-analysis of mean difference. This found a statistically significant between-groups difference of 22 pg ml −1 . Confidence in the result is limited by the small number of studies and by substantial statistical heterogeneity ( I 2  = 94). Conclusion. The clinical value of EBC 8-isoprostane as a quantitative assessment of oxidative stress in asthma remains unclear due to variability in results and methodological heterogeneity. It is essential to develop a robust and standardised methodology if the use of EBC 8-isoprostane in asthma is to be properly evaluated.